Analyzing the corporate social responsibility perception from customer relationship quality perspective. An application to the retail banking sector. (23rd May 2022) - Hobeika, Janine; Khelladi, Insaf; Orhan, Mehmet A.
Abstract: Management scholars are increasingly stressing the importance of corporate social responsibility (CSR) and its growing role in today's business world. Building on stakeholder theory and relationship marketing theoretical framework, this study focuses on the link between customers and CSR and the role of frontline employees in building customer relationship quality, critical for CSR initiatives. This article investigates the effects of expected relational benefits and professional stereotypes on customers' perceptions of companies' CSR activities. This research unveils the cognitive processes influencing customers' perceptions of CSR initiatives the moment they open the companies' doors. A survey was conducted among customers in the banking sector that is experiencing an increasing deployment of CSR programs. We found that frontline employees, as drivers of relational benefits, actively participate in how customers perceive their banks' CSR initiatives. However, how customers perceive their banks through bankers' professional stereotypes partially influences their perceptions of CSR initiatives.